Studies on nano composites of SPEEK/ethylene glycol/cellulose nanocrystals as promising proton exchange membranes - Bano, Saleheen; Negi, Yuvraj S.; Illathvalappil, Rajith; Kurungot, Sreekumar; Ramya, K. (Electrochimica Acta, 2019)
The present work deals with fabrication and characterisations of nano-composite membranes composed of sulfonated poly (ether ether ketone) (SPEEK) cross-linked and reinforced with ethylene glycol (EG) and cellulose nanocrystals (CNCs) respectively. The thin films of cross-linked composite membranes were prepared by solvent casting method and further analysed for physicochemical and electrochemical properties to execute their applicability as promising proton exchange membrane (PEM) in fuel cells. The process of cross-linking helps to improve the strength and dimensional stability of bare SPEEK membranes without compromising with conductivity. However, presence of CNCs further improves the strength and provides an effective pathway for the conduction of protons in membranes by interacting through their surface hydroxyl and sulfonic acid groups with ionic moieties of polymer matrix. All prepared composite membranes showed good oxidative and thermal stability along with good proton conductivity. The cross-linked SPEEK membranes with 4 wt% loading of CNCs possess an appreciable proton conductivity of 0.186 S/cm at 95 degrees C and 95% RH which is comparable to Nafion 117. From the view point of above studies, the prepared nano-composite can be described as promising proton exchange membrane for fuel cells. (c) 2018 Elsevier Ltd. All rights reserved.
Keywords: Cellulose nanocrystals; Cross-linked SPEEK; fuel cell; oxidative stability; proton conductivity